An Extended Fuzzy VIKOR Method with Dynamic Criteria Weight Adjustment for Sustainable Decision Making under Uncertainty with a case study on green supplier selection for sustainable manufacturing - Nahakpam Roshni Devi; M.Kuber Singh; Yengkhom Robert Meetei (Utilitas Mathematica, 2025)
This paper proposes an extended Fuzzy VIKOR method designed to enhance decision-making in uncertain and complex environments. The approach integrates a hybrid criteria weighting scheme preferences by introducing a dynamic criteria weight adjustment mechanism that integrates both subjective expert judgment and objective entropy-based information. A tunable parameter is employed to balance the influence of subjective and objective weights. Interval-Valued Fuzzy Numbers (IVFNs) are employed to capture linguistic uncertainty in the evaluation process. The method is applied to a green supplier selection problem involving four alternatives and five sustainability criteria, demonstrating its applicability to sustainable supply chain management. A sensitivity analysis with respect to the compromise parameter validates the robustness and consistency of the model. The results highlight its practical applicability for sustainability-driven decisions under uncertain conditions